Sex Differences in Lipid Metabolism: Implications for Systemic Lupus Erythematosus and Cardiovascular Disease Risk - Robinson, George A.; Pineda-Torra, Ines; Ciurtin, Coziana; Jury, Elizabeth C. (Frontiers in Medicine, 2022)
It is known that healthy women during childbearing years have a lower risk of cardiovascular disease (CVD) and coronary heart disease compared to age matched men. Various traditional risk factors have been shown to confer differential CVD susceptibilities by sex. Atherosclerosis is a major cause of CVD and mortality and sex differences in CVD risk could be due to reduced atherogenic low and very low-density lipoproteins (LDL and VLDL) and increased atheroprotective high density lipoproteins (HDL) in women. In contrast, patients with systemic lupus erythematosus (SLE), a chronic inflammatory disease that predominately affects women, have an increased atherosclerotic and CVD risk. This increased CVD risk is largely associated with dyslipidaemia, the imbalance of atherogenic and atheroprotective lipoproteins, a conventional CVD risk factor. In many women with SLE, dyslipidaemia is characterised by elevated LDL and reduced HDL, eradicating the sex-specific CVD protection observed in healthy women compared to men. This review will explore this paradox, reporting what is known regarding sex differences in lipid metabolism and CVD risk in the heathy population and transgender individuals undergoing cross-sex hormone therapy, and provide evidence for how these differences may be compromised in an autoimmune inflammatory disease setting. This could lead to better understanding of mechanistic changes in lipid metabolism driving the increased CVD risk by sex and in autoimmunity and highlight potential therapeutic targets to help reduce this risk.